Synergistic Effects of Paenibacillus polymyxa NBmelon-1 Inoculation and Grafting Restructure of Rhizosphere Microbiome and Enhanced Disease Resistance in Melon Self-Rootstocks - Wenjie Dong; Quanyu Zang; Yuhong Wang; Erlei Ma; Weihong Ding; Leiyan Yan; Fangmin Hao (Microorganisms, 2025)
Rhizosphere microorganisms play pivotal roles in mitigating the challenges associated with continuous cropping in melon cultivation. While grafting and plant growth-promoting rhizobacteria (PGPR) independently influence rhizosphere microbial communities, their combined effects remain largely unexplored. This study investigates the synergistic regulation of Paenibacillus polymyxa NBmelon-1 inoculation and grafting on rhizosphere microbiome assembly, plant performance, and disease resistance in melon self-rootstocks. Field experiments demonstrated that NBmelon-1 inoculation significantly enhanced rootstock stem diameter (95.3% increase in spring) and root development, achieving a graft survival rate exceeding 95%. The combined treatment (NB+GJ) increased scion fruit yield by 29.8% in autumn and 36.5% in spring, as well as the single-fruit weight by 22.5% in autumn and 37.3% in spring, while maintaining fruit morphology. Integrated 16S rRNA and ITS sequencing revealed that the NB+GJ treatment selectively enriched antagonistic bacterial phyla (e.g., Firmicutes and Actinobacteriota) and suppressed pathogenic fungi (e.g., Fusarium and Melanconiella). Seasonal shifts in microbial diversity and functional gene profiles underscored the dynamic interplay between treatments and environmental factors. These findings establish a novel strategy for optimizing melon self-rootstock grafting systems and sustainably managing soil-borne diseases.